KAJIAN FORMULASI PUPUK ORGANIK CAIR KEONGMAS (Pomacea canaliculata) TERHADAP PERTUMBUHAN, HASIL DAN KUALITAS KANGKUNG DARAT (Ipomoea reptans Poir) - mohammad zubaidil asrori (AGRONISMA, 2020)
Golden snails has become a pest for farmers, mostly rice farmers, therefore, it is necessary to conduct research of keongmas utilization as a liquid organic fertilizer (LOF). The study was conducted at the third floo screenhouse of Agriculture faculty University of Islam malang. , with the altitude ±400 meters above sea level, the temperatures between 22.7 ° C - 25.1 ° C, and the rainfall reaches an average ranging from 0-20 mm per year. The study was conducted in August - September 2019. This study used a single factor of simple randomized block design with consints of 9 levels : a dose without LOF, 0% LOF meat + 25% LOF shell, 0% LOF meat + 50% LOF shell , 25% LOF meat + 0% LOF Shell, 25% LOF meat+ 25% LOF Shell, 25% LOF meat + 50% LOF shell, 50% LOF meat + 0% LOF shell, 25% LOF meat + 25% LOF shell , and 50% LOF meat + 50% LOF shell. The results of research showt that application of golden snail LOF based on meat and shell have no significant effect on growth, yield and quality of Ipomoea aquatic. This is caused by the low quality of the LOF used in this research.